Short stories: for creative language classrooms - Collie, Joanne; Slater, Stephen (New York: Press Syndicate of the University of cambridge, 1995)
Contains: Very short but unabridged stories with a wide variety of themes - a range of authors from different countries, including leonora corrigton, alasdair gray and peter carey - activities before, during and after reading - a creative development section at the and of each unit to extend the themes and the reader's involvement with the story - notes on the authors and stories, and notes for the teacher on using the material.
Keywords: English Language Texbooks; Languaje